SELF-REGULATED LEARNING (SRL) MAHASISWA INSTITUT ISLAM MAMBAUL ULUM SURAKARTA DI MASA PANDEMI COVID-19 - Fatma Sukmawati (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
Self-Regulated Learning is important for students, especially when learning is carried out online. This study aims to determine the picture of student self-regulated learning in the lecture process during the pandemic. The online lecture process indirectly makes students adapt to the new learning process. This research method is a quantitative descriptive study with research subjects as many as 70 students of the Islamic Institute of Mamba‟ul „Ulum Surakarta (IIM). The results showed that the Self-Regulated Learning of IIM students was in the Very High (ST) category of 10% or as many as 7 students, for the High Category (T) by 30% or as many as 21 students, the Medium (S) category was 45% or as many as 32 students and the Low (R) category is 15% or as many as 10 students and the Very Low (SR) category is 0%. This shows that there is still need for learning adaptation for students during the pandemic period and there is a need for good Self-Regulated Learning in themselves.